Performance of Nickel Foam (NF) Cathode in Microbial Electro-synthesis System for Generating Methane and Acetate Production from CO2 - Satar, Ibdal; Ahmed, Waled Abdo; Juwitaningtyas, Titisari; Syamsuddin, Arief; Majlan, Edy Haryanto; Bakar, Mimi Hani Abu; Kim, Byung Hong (Magister Program of Material Science, Graduate School of Universitas Sriwijaya, 2025)
The cathode material is one of the key factors in enhancing the overall performance of microbial electrosynthesis system (MES). Nickel-based materials are the best option for cathodes in MES due to their excellent catalytic activity. This study aims to evaluate the performance of nickel foam (NF) as self-cathode material in MES for acetate production from CO2. A biocatalyst at the cathode was provided using a mixed-culture of anaerobic sludge from palm oil mill effluent (POME). The field emission scanning electron microscopy (FE-SEM) was used to analyze the cathode surface morphology, while high-performance liquid chromatography (HPLC) was used to quantify the volatile fatty acids (VFAs) in the effluent. The results indicate that the self-cathode NF exhibited excellent performance, achieving an acetate production rate (QAcetate) of 46.0 mM/d, compared to 41.7 mM/d with a graphite felt (GF) cathode at a cathode potential of -0.8 V. Additionally, the self-cathode NF in the MES system demonstrated a coulombic efficiency (CE) of approximately 22.9%. Moreover, the type of cathode material and the microbial community attached to the cathode surface significantly influenced MES performance.